An Application of Solid State Fermentation and Elicitation with Some Microbial Cells for the Enhancement of Prodigiosin Production by Serratia marcescens - Luti, Khalid J K; Yonis, Reem W; Mahmoud, Samer T (Al-Nahrain Journal of Science, 2018)
The present study provides an evidence for the successful utilization of interspecies interactions to enhance antibiotic production in solid state fermentation that previously established in liquid cultures. Ground corn, wheat bran, rice husk and soya bean ground were examined in order to choose the substrate that support the prodigiosin production from Serratia marcescens. Results revealed that maximum production of prodigiosin was obtained in wheat bran medium, starting from early hours of incubation and reaching its maximum of product yield 47.5 mg.gds-1 (mg per gram of dry substrate) after 48 h of incubation. An enhancement by 2.3-fold in prodigiosin production was obtained as a result of introducing, separately, live and dead prokaryotic and eukaryotic microbial cells as elicitors to S. marcescens medium. The highest prodigiosin production (240mg.gds-1) was obtained when S. marcescens was cultured in wheat bran medium supplemented with sunflower oil (0.5ml.g-1 substrate) and live cells of Bacillus subtilis (0.4ml.g-1 substrate) as elicitor.